Some Morphological Variations in The Land Snail Monacha cantiana (Montagu,1803) within Baghdad Province (Baghdad Science Journal, 2013)
The present work includes investigation of some features of shell morphology; shell size, shell thickness, shell colour of the land snail Monacha cantiana, in addition to the correlation between height and diameter of shell and between shell aperture diameter and shell diameter at four sites within Baghdad Province, Iraq. Also, measurements of three environmental variables were made; soil temperature, soil moisture and soil calcium content in adition to population density. Shell Aperture Index (Ia) and Shell Index (SI) for individuals from size class ranged between (9-12)mm were measured. The results showed that the deference in shell size by using (Ia) within population related to temperature, moisture and population density but, the value of Shell Index decreased in AL-Kadhimiya site (0.81-0.97) due to increase in population density. The species was characterized by shell colour variation (creamy white, white ,creamy). Also, The results showed strong and positive correlation between shell height and diameter and between shell aperture diameter and shell diameter for all size classes.